2019
DOI: 10.5530/ijpcs.2019.8.17
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of the Pharmacokinetics Services at the Ministry of Health Hospitals in Saudi Arabia: Drug Therapy Monitoring and Healthcare Professional Education

Abstract: Objectives: A clinical pharmacist offers vital support in the expansion of a final prescription with improved patient management and enhanced safety. The aim of the current study to explore the Pharmacokinetics services at Ministry of Health (MOH) hospitals in Saudi Arabia with an emphasis on drug therapy monitoring and patient's education. Methods: This is a 2-months cross-sectional national survey related to the Pharmacokinetics services with a focus on drug therapy monitoring and education of pharmacist at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Moreover, the physicians did not fully practice the reporting of adverse drug reaction during pharmacokinetics services and did not perform cost analysis. In addition to the annual plan of the pharmacokinetic program as previously reported [13,15], which shows insufficient practice of essential elements of pharmacokinetics services. Furthermore, the pharmacokinetic deficits of the annual review and future vision as previously reported [15].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, the physicians did not fully practice the reporting of adverse drug reaction during pharmacokinetics services and did not perform cost analysis. In addition to the annual plan of the pharmacokinetic program as previously reported [13,15], which shows insufficient practice of essential elements of pharmacokinetics services. Furthermore, the pharmacokinetic deficits of the annual review and future vision as previously reported [15].…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have reported on the impact of involvement of pharmacists in the therapeutic drug monitoring and pharmacokinetics services [7][8][9][10][11]. Other studies have investigated the pharmacokinetics survey services at various healthcare organizations [12][13][14][15][16][17][18][19]. However, to the best of our knowledge, there are only a few local studies conducted to assess the practice of pharmacokinetics services by physicians across Middle Eastern countries [20,21].…”
Section: Introductionmentioning
confidence: 99%